1998
DOI: 10.1007/bf02447314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytokines on the generation of active oxygen species by pulmonary and peripheral blood phagocytes

Abstract: The effect of naturally occurring cytokines on the chemiluminescence response of neutrophils from bronchoalveolar lavage and peripheral blood was studied in patients with chronic bronchitis. It was found that the response of neutrophils from bronchoalveolar lavage differs from that of peripheral blood neutrophils. The cytokines prestimulated the peripheral blood neutrophils for chemiluminescence. Key Words: cytokines; chemiluminescence; chronic bronchitisBronchoalveolar neutrophils and macrophages act as effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…These studies were grouped by their system of research. The most commonly studied system of research was blood cells (9) [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] followed by whole body (8) [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , blood plasma (4) [39] , [57] , [58] , [59] , tissues (2) [60] , [61] , urine (2) [62] , [63] , saliva (1) [64] , and other cells (1) [65] .…”
Section: Resultsmentioning
confidence: 99%
“…These studies were grouped by their system of research. The most commonly studied system of research was blood cells (9) [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] followed by whole body (8) [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , blood plasma (4) [39] , [57] , [58] , [59] , tissues (2) [60] , [61] , urine (2) [62] , [63] , saliva (1) [64] , and other cells (1) [65] .…”
Section: Resultsmentioning
confidence: 99%
“…When researchers established links among oxidation, free radical production, and an increase in BE, this led to further investigation of using BE as a means to measure an individual’s health ( E. P. Wijk & Wijk, 2005 ; R. Van Wijk, 2001 ). Recent studies have shown an association of increased BE in multiple sclerosis patients ( Hammann et al, 1987 ), ankylosing spondylitis ( K. J. Ho et al, 2000 ), and in chronic lung disease ( Koval’chuk et al, 1998 ). This increase in BE during stress, illness, and disease ( Grasso et al, 1992 ; Keshavarzian et al, 1992 ; E. P. Van Wijk et al, 2010 ) corresponds to a number of studies that show that BE decreases in healthful behavior such as meditation ( E. P. Van Wijk et al, 2006 ; E. P. Van Wijk et al 2008a ; E. P. Van Wijk et al, 2008b ).…”
Section: Introductionmentioning
confidence: 99%